Evaluation of High Doses of Phytase in a Low-Phosphorus Diet in Comparison to a Phytate-Free Diet on Performance, Apparent Ileal Digestibility of Nutrients, Bone Mineralization, Intestinal Morphology, and Immune Traits in 21-Day-Old Broiler Chickens - Beatriz Martínez-Vallespín; Klaus Männer; Peter Ader; Jürgen Zentek (Animals, 2022)
The supplementation of feed with phytases enables broilers to utilize more efficiently phosphorus (P) from phytic acid (IP6), the main storage form of P in plants. The current study evaluated the addition of 500, 1000, and 3000 FTU of phytase per kg to a phytate-containing diet with low P level (LP) fed to broilers from 1 to 21 days of age and compared it to a hypoallergenic phytate-free diet (HPF). There was a linear improvement in performance parameters with increasing levels of phytase in the LP diet (p < 0.001). Apparent ileal digestibility of crude protein, P, and some amino acids, increased with phytase. Crude ash, P, and the calcium content of tibia bones linearly increased with increasing levels of phytase (p < 0.001). Crypt depth (related to body weight) in the jejunum epithelium linearly decreased with phytase addition (p < 0.001). Cecal crypt depth decreased with phytase supplementation (p = 0.002). Cecum tissue showed lower counts of CD3-positive intraepithelial lymphocytes in broilers receiving the phytase in comparison to LP (p < 0.001), achieving similar counts to HPF-fed broilers. Although results from the current study seem to point out some mechanisms related to the immune response and mucosal morphology contributing to those overall beneficial effects, no clear differences between different phytase doses could be demonstrated in these specific parameters.